2017
DOI: 10.1093/abbs/gmx020
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant CC16 protein inhibits the production of pro-inflammatory cytokines via NF-κB and p38 MAPK pathways in LPS-activated RAW264.7 macrophages

Abstract: Accumulating evidence indicates that Clara cell protein-16 (CC16) has anti-inflammatory functions, although the involved molecular pathways have not been completely elucidated. Here, we evaluated the effect of recombinant rat CC16 (rCC16) on the expression of tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), and IL-8 in lipopolysaccharide (LPS)-stimulated mouse macrophages (RAW264.7 cells) and explored the underlying molecular mechanisms. It was found that rCC16 inhibited LPS-induced TNF-α, IL-6, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 40 publications
5
35
0
Order By: Relevance
“…Previous studies have revealed that NF‐κB signaling pathway is one of the most important pathways that are activated in macrophages under the pathogen challenge . Thus, we aimed to study whether the anti‐inflammatory ability of curcumin is associated with NF‐κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that NF‐κB signaling pathway is one of the most important pathways that are activated in macrophages under the pathogen challenge . Thus, we aimed to study whether the anti‐inflammatory ability of curcumin is associated with NF‐κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that NF-κB signaling pathway is one of the most important pathways that are activated in macrophages under the pathogen challenge. [34][35][36][37][38] Thus, we aimed to study whether the anti-inflammatory ability of curcumin is associated with NF-κB signaling pathway. By examining the protein expression levels via Western Blotting, we found that IAV infection leads to the decrease in IκBα and cytosolic p65, while enhanced the levels of p-IκBα and nuclear p65.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear translocation of NF-kB, which dissociated from its inhibitory protein IkB, is the most crucial step for NF-kB signaling activation. 33 It has been found that LCP-3 suppresses LPS activated NF-kB signaling by inhibiting phosphorylation of IkBa. Moreover, LCP-3 attenuates the phosphorylation of IKKa/b in both types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…As an immunoregulatory protein, CC16 executes an anti-inflammatory function by inhibiting phospholipase A2 activation and promoting the expression of inflammatory cascades (IL-1b, IL-8, et al), TH2 cell differentiation, and the migration of neutrophils and monocytes [23,24]. Consistent with these studies, Pang demonstrated that recombinant rat CC16 protein inhibits LPS-induced MMP-9 expression and the production of pro-inflammatory cytokines via NF-κB pathway in model of tracheal epithelial cells and RAW264.7 macrophages [25,26]. She suggested that exogenous supplementation of recombinant CC16 ameliorates cigarette smoke-induced lung inflammation in a murine disease model of chronic obstructive pulmonary disease [27].…”
Section: Discussionmentioning
confidence: 89%